A simple and fast method for the fabrication of p-type β-Ga2O3 by electrochemical oxidation method with DFT interpretation. (12th February 2023) - Deng, Zu-Yin; Kumar, Utkarsh; Ke, Chia-Hsin; Lin, Chin-Wei; Huang, Wen-Min; Wu, Chiu-Hsien
Abstract: In this work, a simple electrochemical oxidation method has been used to prepare p-type β -Ga2 O3 nanoparticles. This method overcomes the problem of doping high energy gap semiconductors to form p-type. The electron holes of β -Ga2 O3 were caused by oxygen vacancy (Vo) and showed the shorter lattice constant and preferred orientation in XRD analysis. The peak area of oxygen vacancy also reflects a higher ratio than n-type Ga2 O3 in x-ray photoelectron spectroscopy (XPS). The adsorption of reducing gas (CO, CH4, and H2 ) enhanced the resistance of the β -Ga2 O3 confirming the p-type character of NPs. The DFT calculations showed that oxygen vacancy leads to higher energy of the Fermi level and is near the valence band. The binding energy of Ga2 O3 and after interaction with gas molecular was also calculated which is analogous to our experimental data.